MATLAB programming - Singh, Y. Kirani & Chaudhuri, B.B (Prentice-Hall of India, 2007)
This book introduces MATLAB programming in simple language with numerous examples that help Clarify the concepts. It is designed to enable readers develop a strong working knowledge of MATLAB and acquire programming skills to write efficient programs.